Evaluation of antibacterial effects of pulp capping agents with direct contact test method - Yalcin, Muhammet; Arslan, Ugur; Dundar, Ayse (European Journal of Dentistry, 2014)
Objectives: Calcium hydroxide has been used in dentistry as a major capping material having the capacity to introduce the formation of a mineralized dentin bridge, but it has no direct inducing effect to the pulp cells. The purpose of this study was to evaluate the antibacterial properties of three different pulp capping agents using a direct contact test (DCT). Materials and Methods: The antibacterial properties of three pulp capping agents were evaluated a DCT. For the DCT, wells (n = 12) of 96-microtiter plates were coated with the tested cements (Dycal, Dentsply, USA; DiaRoot BioAggregate, Diadent, Holland; Calcimol LC, Voco, Germany) and Kalzinol (zinc oxide/eugenol cement, Dentsply, USA) was used as control material. A Lactobacillus casei suspension was placed on the surface of each specimen for 1 h at 37°C. Bacterial growth was monitored for 16 h with a temperature-controlled microplate spectrophotometer. The kinetics of the outgrowth in each well were recorded continuously at 650 nm every 30 min. The data were analyzed by one-way ANOVA, and Tamhane's T2 multiple comparison test. The level of significance was determined as P < 0.05. Results: All pulp capping agents showed an increase in the logarithmic growth rate of L. casei when compared with the control group (P < 0.05). Therefore, all pulp capping agents did not show antibacterial activity. Conclusions: The tested pulp capping agents haven't got antibacterial properties. Therefore, they should be used carefully when pulp is exposed or only very thin dentin remained over the pulp to avoid bacterial contamination.
Keywords: Antibacterial effects; bacteria; direct contact test; pulp capping agents